Peculiarities of the Tourism Industry Development of the Mediterranean and Aegean Coasts of Turkey - Liudmyla Niemets; Ievgeniia Telebienieva; Taras Pohrebskyi; Iryna Scryl; Hanna Kucheriava; Yanina Vasylevska (Communications of International Proceedings, 2021)
The tourism industry is becoming increasingly important in the economies of most countries. Over the last decade, the world tourism market has grown, and even in times of crisis, it has remained a reliable sector of the economy. In 2019, the World Tourism Organization (UNWTO) registered 1.5 billion international tourist trips worldwide. At the same time, for some countries the tourism industry is especially important for the development of the country's economy and its human resources, solving many socio-demographic problems. Turkey is one of such countries and occupies a leading position in the modern tourism industry. The fact that country continues developing, despite the negative effects of the economic crisis of 2007-2008 is an indicator of the country's success in tourism. Turkey is a country with large tourist and recreational resources. Despite the misconception that this whole country exists solely through tourism, Turkey is not on the list of countries with a high share of tourism in GDP. According to the Turkish Institute of Statistics (TÜİK), the share of tourism in Turkey's GDP has fluctuated between 2.6 and 3.9% over the last 10 years. However, tourism is one of the most dynamically developed sectors of the Turkish economy. A large number of unique historical monuments in Turkey, the exceptional beauty of the Mediterranean beaches, favorable climatic conditions, favorable geographical location – all this opens wide prospects for the tourism business. Turkey ranks ninth in the ranking of the world's leading countries in terms of tourist arrivals. The Mediterranean and Aegean coasts of Turkey ensure the development of the country's tourism industry, which, in turn, determines the relevance of this topic.
Keywords: Tourism; tourism industry; the Aegean and Mediterranean coasts of Turkey.